When Opportunity Knocks: Confronting Theory and Empirics about Dynamics of Gender Wage Inequality - Joanna Tyrowicz; Lucas van der Velde (Institute of Labor Economics (IZA), 2021)
We present empirical evidence that large structural shocks are followed by changes in labor market inequality. Specifically, we study short-run fluctuations in adjusted gender wage gaps (unequal pay for equal work) following episodes of structural shocks in the labor markets, using several decades of individual data for a wide selection of transition countries. We find that for cohorts who entered the labor market after the onset of transition. Labor market shocks lead to significant declines in the gender wage gap. This decrease is driven mostly by episodes experienced among cohorts who enter the labor market during the transition. By contrast, we fail to find any significant relation for cohorts already active in the labor market at the time of transition. We provide plausible explanations based on sociological and economic theories of inequality.
Keywords: C24; J22; J31; J71; 330; gender wage gap; transition; non-parametric estimates; worker flows